1996
DOI: 10.3109/10641969609097910
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin: Changes in Circulating and Cardiac Tissue Concentration in Dahl Salt-Sensitive Rats on a High-Salt Diet

Abstract: Adrenomedullin (AM), a novel hypotensive peptide, is suggested to be involved in defense mechanisms against hypertension, however, the detail mechanisms have not been clarified. To elucidate whether AM synthesis would be altered in a salt dependent hypertension, we have investigated the AM concentration and AM messenger RNA (mRNA) level in tissues of Dahl salt-sensitive rats on either low- or high-salt intake. The AM concentration in cardiac ventricle of the high-salt group was significantly higher than that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 25 publications
0
23
1
Order By: Relevance
“…Our results are inconsistent with those of previous studies of other hypertensive rat models, such as renovascular hypertensive rats (10), Dahl-salt sensitive rats (11), and pulmonary hypertensive rats (12). The assay system that we used to measure rat AM was the same as that used in earlier studies, and the plasma AM levels in WKY/ Izm were similar to those reported in other normotensive rats (4).…”
Section: Discussioncontrasting
confidence: 57%
“…Our results are inconsistent with those of previous studies of other hypertensive rat models, such as renovascular hypertensive rats (10), Dahl-salt sensitive rats (11), and pulmonary hypertensive rats (12). The assay system that we used to measure rat AM was the same as that used in earlier studies, and the plasma AM levels in WKY/ Izm were similar to those reported in other normotensive rats (4).…”
Section: Discussioncontrasting
confidence: 57%
“…These findings are consistent with previous observations in DS rats at the CHF stage. 27 In the present study, we extended our investigation to include the AM receptor system and 2 molecular forms of AM in the failing LV and found that the AM receptor components, CRLR, RAMP2, and RAMP3, were maintained at higher levels in the progression to HF. Recent studies showed that gene expression of RAMP2, CRLR, and AM in the ventricles of rats with old myocardial infarction were increased compared with those of shamoperated rats.…”
Section: Further Activation Of Am System During Transition To Chfmentioning
confidence: 94%
“…In addition, recent studies have shown that the plasma concentration of AM was increased in patients with congestive heart failure (16,17), and that AM immunoreactivity was markedly increased in the failing heart ventricle (18). AM expression was also shown to be increased in rat hypertrophic ventricles (19,20). These findings suggest that AM levels in the heart may be correlated to the degrees of congestive heart failure or cardiac hypertrophy.…”
Section: Cardiovascular Tissuementioning
confidence: 86%